2006
DOI: 10.1136/aim.24.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Central Pain Affecting the Ribcage following Traumatic Brain Injury and Rib Fractures – a Case Report

Abstract: This case report describes the use of acupuncture in the management of chronic central pain in a 51 year old man following severe traumatic brain injury and multiple injuries including rib fractures. The patient reported rapid and significant improvements in pain and mood during a course of acupuncture treatment. Chronic pain following traumatic brain injury is a significant problem. Chronic pain after rib fractures is also commonly reported. Acupuncture is widely used in the management of pain but its use has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…An evidence class II study using EEG recordings with photic biofeedback in 12 patients with cognitive difficulties did include a waitlist control, showing a significantly greater decrease in depression scores in the biofeedback group (Schoenberger et al, 2001). A case report of classical Chinese acupuncture in a patient with severe TBI, multiple injuries, and severe pain showed improvement in pain, but not depression or anxiety scores (Donnellan, 2006).…”
mentioning
confidence: 99%
“…An evidence class II study using EEG recordings with photic biofeedback in 12 patients with cognitive difficulties did include a waitlist control, showing a significantly greater decrease in depression scores in the biofeedback group (Schoenberger et al, 2001). A case report of classical Chinese acupuncture in a patient with severe TBI, multiple injuries, and severe pain showed improvement in pain, but not depression or anxiety scores (Donnellan, 2006).…”
mentioning
confidence: 99%
“…A placebo-controlled, blinded trial of homeopathy for mild TBI showed significant symptom reduction in the treatment group vs. control [35], though a later review of this study from a WHO Task Force on TBI withheld recommending homeopathic treatment for TBI because of need for and challenge inherent in replication, given the individualized nature of homeopathy [36]. Studies of acupuncture [37][38][39] have noted significant support for its use in the treatment of TBI, for a range of TBI severities and symptoms. Tai Chi has also been studied, using a wait-list or social-interaction control, and the initial results appear promising in terms of outcome measures related to mood and selfesteem [40,41].…”
Section: International Journal Of Physical Medicine and Rehabilitationmentioning
confidence: 93%
“…The successful use of acupuncture for treating TBI-related pain, spasticity and altered level of consciousness has been reported in several studies (Donnellan 2006; Tamai et al 2007). In one randomized trial of 30 individuals in post-traumatic coma, 15 subjects received routine medical care combined with acupuncture and point injection therapy while 15 controls received only standard treatment (He et al 2005).…”
Section: Alternative and Complementary Treatmentsmentioning
confidence: 98%